A mild form of adenylosuccinate lyase deficiency in absence of typical brain MRI features diagnosed by whole exome sequencing - Marina Macchiaiolo; Sabina Barresi; Francesco Cecconi; Ginevra Zanni; Marcello Niceta; Emanuele Bellacchio; Giacomo Lazzarino; Angela Maria Amorini; Enrico Silvio Bertini; Salvatore Rizza; Benedetta Contardi; Marco Tartaglia; et al. (BMC, 2017)
Abstract Background Adenylosuccinate lyase (ADSL) deficiency is a defect of purine metabolism affecting purinosome assembly and reducing metabolite fluxes through purine de novo synthesis and purine nucleotide recycling pathways. The disorder shows a wide spectrum of symptoms from slowly to rapidly progressing forms. The most severe form is characterized by neonatal encephalopathy, absence of spontaneous movement, respiratory failure, intractable seizures, and early death within the first weeks of life. More commonly, ADSL presents purely neurologic clinical picture characterized by severe psychomotor retardation, microcephaly, early onset of seizures, and autistic features (type I) or a more slowly progressing form with later onset, and major features including slight to moderate psychomotor retardation, and transient contact disturbances (type II). Diagnostic markers are the presence of succinylaminoimidazole carboxamide riboside (SAICAr) and succinyladenosine (SAdo) in extracellular fluids. ADSL is a rare disorder, although its prevalence remains unknown. Of note, the wide range of essentially nonspecific manifestations and lack of awareness of the condition often prevent diagnosis. Case presentation We present here the case of particularly mild, late onset ADSL that has been unsuccessfully investigated until whole exome sequencing (WES) was performed. Conclusions Besides emphasizing the valuable diagnostic value of WES, this report provides new data further documenting the relatively wide clinical manifestation of ADSL.